A Single Bangle Does Not Jingle: The Twinning Imperative of Ubuntu - Nokuthula Hlabangane (International Journal of Critical Diversity Studies)
Humanity is beset by a number of intractable challenges, most of which can be attributed to the underlying ethos of capitalism. Characterised as “cultures of cruelty” that, together, have wrought untold suffering across the epochs, Ani’s (1993) notion of Yurugu is deployed to begin to account for the proclivity towards this destruction. In a bid to account for resilience against the unyielding odds integral to the notion of the “survival of the fittest”, this paper posits ubuntu and the ethos of interconnection as the bedrock of said resilience. The paper taps into the lived ethos of abantu to argue that decolonisation as a reflection of the lifeways central to the cosmic rhythm is not far off even within the patriarchal, western-centric, colonial Africa. In this way, the ubiquity of the capitalist, instrumentalist, rational reason is routinely undermined as higher ideals are lived, heralding beauty in the desert.